Digon I'r Diwrnod - Evans, Geraint (Y Lolfa, 2018)
Popular author Geraint Evans' fifth novel about Gareth Prior and his team of detectives in the Dyfed-Powys Police Force. The main thread of the story relates to one day, during which a judge and his family are kept captive in his home by two drug dealers.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books